Leadership Oriented: The Role Of Innovative Planning And Work Culture Toward Corporate Productivity - ., Kuswandi; ., Harijono; Handini, Sri; Sanggarwati, Diah Ayu (Archives of Business Research, 2017)
Purpose, This study aims to examine and analyze the level of corporate productivity between the State of Indonesia with Vietnam the role of Leadership oriented through innovative aspects of planning and work cultures in each country. Design / Methodology / Approach, This analysis technique is using Structural Equation Modeling (SEM) with AMOS 18. Sampling is using random sampling on e-commerce the user’s. Respondents from Manager MNC is 9 respondents and employees with a total of 280 respondents obtained after the selection process. Finding and implications, First, that innovative leadership oriented has significant effect on corporate productivity is accepted. Second, it stated that innovative leadership oriented has significant effect on corporate productivity.